Prevalence and characterization of multi-drug resistant Escherichia coli from urine samples (Dhaka University Journal of Biological Sciences, 2011)
Isolation, identification and characterization of Escherichia coli were carried out in terms of biochemical, serological, antibiogram, plasmid profile and culture condition of urine samples. Out of 50 urine samples, 36 were positive for E. coli that were confirmed by biochemical (e.g. oxidase, kligler’s iron agar, indole, methyl red-voges proskauer and citrate utilization) tests and 4-methyl-umbelliferyl-β-D-glucoronide (MUG) test. Twenty seven strains gave positive result with different antisera whereas nine strains were untypable (UT), respectively. Thirty six strains were also tested by antibiogram against ten different antibiotics. Most E. coli strains were resistant to bacitracin, ampicillin, novobiocin, kanamycin and streptomycin. Eighty three per cent strains were sensitive to ciprofloxacin and gentamycin while 11 and 12% showed resistance to ciprofloxacin and gentamycin, respectively. By plasmid profile analysis of the 36 strains seven different plasmid patterns were observed. Comparison of the plasmid profiles with the antibiogram results indicated the presence of resistant (R) plasmid. Thirty four isolates of E. coli contained a common 25 kb plasmid that may possibly be responsible for drug resistance in this study. The results suggested that the prevalence of multi-drug resistant and new serotype of E. coli may be increasing rapidly which is alarming for treatment of urinary tract infection in Bangladesh.Key words: Prevalence; Characterization; E. coli; Multi-drug resistant; Serotype; Clinical sampleDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8834Dhaka Univ. J. Biol. Sci. 20(1): 23-30, 2011 (January)